Professional reflection as a condition of formation of innovational activity of the future teacher - N.M. Chernuha; V.H. Muromets (Academy of Cognitive and Natural Sciences, 2007)
In the article is examined and is determined psychological -pedagogical aspect of forming of professional reflection in the conditions of innovative activity offuture teachers.